PTH-135 Prevalence and treatment of reduced BMD and vitamin D levels in patients assessed for liver transplantation. (22nd June 2015) - Dsouza, S; Garner, M; Westbrook, R
Abstract : Introduction: Patients with end stage liver disease are at risk of reduced BMD due to a combination of associated metabolic, endocrine and nutritional deficiencies. Liver Transplantation (LT) results in a short term further loss of BMD and patients are at risk of fractures associated with a morbidity and mortality. Method: All patients admitted for a liver transplant (LT) assessment from February 2012 to March 2013 underwent BMD testing and vitamin D testing. Results were correlated with aetiology and severity of underlying liver disease. Results: In total 109 patients were included. Primary disease aetiology was alcohol (33%), viral (23%), NASH (9%), cholestatic (16%), AIH (6%), and other (13%). The median UKELD score was 55 (range 42–74). Nine patients (8%) were on bone protection prior to LT assessment. At the time of LT assessment 79 (72%) patients were either osteoporotic (n = 25) or osteopenic (n = 54) based on their DEXA T score. A higher UKELD score was significantly associated with a lower T score (p < 0.001). Vitamin D levels were measured in 92/109 patients, of these 79% (n = 73) of patients had vitamin D deficiency (<75nmol/L) with 50% being severely deficient (Vitamin D <35nmol/L). The severity of vitamin D deficiency was not associated with a higher UKELD score (p = 0.16). Disease aetiology was not significantly associated with either vitamin D deficiency or the presence of reduced bone mineral density. Thirty-four of the 73 patients with vitamin D deficiency were commenced on vitamin D therapy. Of the 25 patients with osteoporosis only 1 patient was commenced on a bisphosphonate and a further 9 patients received calcium and/or vitamin D therapy. Conclusion: We conclude that Vitamin D deficiency and osteoporosis/osteopenia are both very common in patients being considered for LT. Due to the increased risk of falls in patients with CLD and the further loss of BMD at the time of transplant we propose that all patients being assessed for transplant should be screened for vitamin D deficiency and a reduced BMD during the liver transplant assessment process and treated aggressively. Disclosure of interest: None Declared.